(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The ideas of a world-famous novel with its mysticism and terror can be difficult to swallow when seen on the surface. However, the thoughts of Mary Shelley are immediately known when the text has understood in a contrapuntal light. In light of colonialism, the question of colonialism is arose. In the English canon, Frankenstein takes on a much deeper meaning. It’s not the novel that is limited to wonderful stories on holiday; no, instead, it reveals the issues in both colonized and colonizer people minds. This story is intertwined in the structure of our times and not in a far-flung world. Frankenstein is a story that challenges the convictions and ideologies of a whole world and culture. This article will explain appeared and conventions of colonial literature—also, Victor Frankenstein and Lavenza and monster